KESESUAIAN LAHAN DAN POTENSI PRODUKSI TANAMAN GAMBIR DI KABUPATEN PESISIR SELATAN SUMATERA BARAT - J Juniarti; Y Yuzirwan; Dian Fiantis (Jurnal Solum, 2004)
The land suitability study for gambir crop (Uncaria gambir, Roxb) in the buffer zone of the National Park of Kerinci Seblat (Taman Nasional Kerinci Seblat) at Salido Saribulan, sub district IV Jurai, Pesisir Selatan was investigated. The objective of this study was to estimate the land suitability for gambir in Salido Saribulan. The soils were sampled in composite ways for analyses in laboratory. The results showed that according to climatic and physical land condition, the studied area was considered as class S1 (highly suitable). However, based on land suitability class, it was grouped as S3f (marginally suitable with some constraints in the availability of soil nutrients). We suggested that to increase gambir production in the studied area can be done by adding some fertilizers both organic and inorganic ones.